Epidemiological Study of Patients with Prostate Cancer in South of Iraq - Al-Tmemi, Manal Badi Salih (University of Thi-Qar Journal of Science, 2019)
The present study was designed to investigate some epidemiological and serological study, in a sample of Thi-Qar, Basarh, Missan provinces south of Iraq. The sample included (32) patients, who were attending the (Basrah oncology and hematology center) in Basrah province , (Clinical oncology unit) at Thi-Qar province and (AL-Shefaa oncology center) at Misan province .The diagnosis was made by the consultant medical staff, which was based on a history inspection, clinical examination and evaluations of serum PSA level. The epidemiological results revealed that there were a significant differences in the distribution of prostate cancer, where Basrah province recorded the highest percentage ( 75% ) of prostate cancer in comparison with Thi- Qar in percent ( 15.6% ) , and ( 9.3%) in Missan. Our results revealed the highest number of patients filled in age (60-69) years and age (≥ 70) years, and low numbers in age group(50-59) years represented by (43.75, 40.62, and 15.62%, respectively). The serological study revealed that PSA level was increased with age, where the PSA level (>20 ng/ml) recorded the highest percentage (25%) by agegroup (≥ 70) years and followed by age group (60-69) years which recorded (18.7%), while the age group (50-59) years not recorded any percentage in PSA level (>20 ng/ml).